Castniinae (lepidoptera: castniidae) from Venezuela. III: Genera represented by only one known species. - Gonzáles, Jorge (Ciencia, 1970)
A list of six species belonging to genera of Castniinae (Lepidoptera: Castniidae) represented in Venezuela by only one species is presented herein. General comments on the importance and difficulties on studying the family are given. A diagnosis to help on identification and comments on each species are provided. Examined material from different Venezuelan collections are also presented.